Improving the Production of Phenolic and Flavonoid Compounds in Suspension Cell Cultures of the Plant Salvia compressa Endemic to Iraq Using Biostimulants - Hasanain A. F. Dhmosh, (American Journal of Biology and Natural Sciences, 2026)
Background: Salvia compressa is a highly valued Iraqi-endemic plant Iraqi-endemic plants containing various polyphenolic and flavonoids compounds. constrained by environmental and seasonal challenges, however, limiting the sustainability and commercial availability. Objective: To assess the effect of different biostimulants on bioaccumulation of these bioactive secondary metabolites in the suspension cell culture of this rare plant. Methodology: Callus cultured from sterile seedlings, suspension cell cultures were established in liquid MS media, and callus was elongated using elicitors such as methyl jasmonate, salicylic acid and yeast extract at different concentrations on the 14th day. An HPLC-DAD method was used for the analysis of results. Results: Production of compounds was greatly stimulated by the use of the biostimulants. Total phenolic content of 31.8 mg/g DW highest among the treatments with 100 μM methyl jasmonate while the flavonoids which doubled to 16.5 mg/g DW demonstrating an improvement over the control. HPLC analyses revealed that, due to treatment with yeast extract, rosmarinic acid increased significantly from 3.1 mg/g in the untreated to 6.9 mg/g, while it increased from 2.4 mg/g to 7.8 mg/g when methyl jasmonate was used. Increases were also found in caffeic acid, salvianolic acid and luteolin in the study. Conclusion: The study reveals that the suspension cell culture in the presence of Biostimulants such as methyl jasmonate is an effective, sustainable platform for the mass production of bioactive compounds from Salvia compressa; indicating its potential for utilization in the pharmaceutical industries.